Jernaldermanden fra Grauballe - Glob, P.V. (Kuml, 1956)
The lron Age Man from Grauballe It is always chance which brings the peat-bog discoveries, the chances generally of peat-cutting or draining. Thus it was, too, on Saturday, 26th April 1952, when a working party in a little peat-bog below the farm of Nebelgaard (reg. no. Nebel 2a) in the parish of Svostrup, Hids Herred, Viborg County, a little over a kilometre from their native village of Grauballe, came upon a well preserved peat-bog body. A human head, dark of feature and short of hair, protruded from the brown peat (Fig. 1). Part of the neck and shoulder lay also uncovered. The head lay to the north, the legs towards the south, and excavation soon showed that the body lay prone, with the left leg outstretched, the right arm and leg bent. The peat-bog is a little circular saucer bog, about 150 metres across, and the place of discovery was on the southeastern side, about 30 metres from the firm land, which slopes evenly down to the bog on every side (Fig. 2). It was moreover clear that the body lay in an ancient pit, as a soft light stratum of sphagnum peat extended both above and below the body (Fig. 1). As soon as it was determined that nothing except peat surrounded the body further investigation on the spot was stopped, and the dead body was taken up together with the whole block of peat in which he rested and transported to the Forhistorisk Museum, where a more detailed investigation could be carried out at leisure. This continued excavation discovered no trace, above the naked male figure which was revealed, of clothes or other objects which might have accompanied him to his resting place in the bog. Clothing of wool or leather would, as we know from corresponding discoveries, have survived, while linen or other vegetable material would without doubt have disappeared, but would probably have left their impress on the skin, which was almost everywhere smooth and unbroken. As no such traces are found it must be assumed that he was deposited in the peat as naked as he came into the world. The whole character of the discovery compels us to attribute the body to the large group of peat-bog bodies from the raised peat-bogs of northwest Europe, a group numbering about 100 bodies in all, of which about 40 come from Denmark, the rest being from northwest Germany and Holland 1). With the exception of a very small group, which appears to be of persons who have ended their days in the bogs as a result of foul play or of accident 2), they must all be classed with the discoveries of sacrificial objects from prehistoric times, and a few of them can, on a basis of the objects which were found with them, be attributed to the period between the end of the Bronze Age and the beginning of the Later lron Age, or in other words to the thousand years from 500 BC to 500 AD 3). To the datings on archeological evidence can be added those based on natural sciences, which also fall within this period 4). In the case of Grauballe Man a peat-geological investigation was made, and would attribute him to the Roman lron Age, the period 0--400 AD, and this agrees with a dating on the basis of radioactive carbon reading to 310 AD ± 100. The position of the dead man is worthy of note, lying prone with the left leg stretched and the right sharply bent, the left arm outstretched and the right bent, a position known from the corresponding discoveries in Borremose. Both the man found in 1947 and the woman found in 1948 lay prone with one leg stretched out and the other bent. The man lay north-south, with his head to the north, as did Grauballe Man, while the woman lay east-west with her head to the east 5). Numerous attempts have been made to interpret the meaning of these peat-bog bodies, which appear to have comprised just as many women as men. The various views fall in the main into two groups, one seeing the peat bodies as evidence of human sacrifice in association with the religious ceremonies of the lron Age, the other interpreting them as executed criminals. In this connection there is reason to draw attention to two peat-bog discoveries, those of the men from Tollund (Fig. 5) and from Borremose (Fig. 6). They possess the common factor that both have been put to death by hanging and deposited in the bog with the rope still around their necks. The two nooses, that from Tollund elaborately plaited and that from Borremose remarkably knotted, bring to mind the torques of the Later Bronze Age and the Early lron Age. They are almost always twisted, as though they were of rope or leather (Fig. 8), and they are found deposited in the peat-bogs, often in pairs, one or more pairs together, though in the Early lron Age it is more usual to find them singly and of such massive types that they can scarcely have been borne by human beings but must have been manufactured for sacrifice or perhaps to adorn images of the gods, carved in wood. The discovery of these rings in the peat bogs, in period 5 of the Bronze Age together with other objects, in period 6 and in the Celtic Iron Age more often alone, has been interpreted by Bror Schnittger in the beautiful image of woman's sacrifice, a prayer for or a thank-offering for a child, offered to the divinities which preside over childbirth, - which might very well be the predecessor to the god Höner in this matter, the stork, whose connection with childbirth has been believed in almost up to our own time 10). To interpret these numerous feminine ornaments as the offerings of women may well be correct, but they may also be general offerings to a female divinity, a divinity which first entered Scandinavia at just this period, the Later Bronze Age (Figs. 9-10). That these female statuettes represent a female fertility divinity like the Near Eastern goddesses Ishtar and Astarte and the Greek goddess of fertility and love Aphrodite, to name merely a few from the large group of similar goddesses, was long ago proposed by T. J. Arne 11). This goddess, who plays the leading role in the great cult-drama which is to ensure the rhythm of cultivation, the corn which is buried in the ground and springs up again to new life with rich increase, and the creative act of love in man and beast, is represented in all the old agricultural cults in the same form, with sexual characteristics emphasised, and with her hands pressed upon the lifegiving springs, the breasts. In the southeastern part of Central Europe she reaches the Danube valley together with the culture of the cultivators 12). She perhaps first reached Scandinavia in the Bronze Age, to which the female statuettes of Denmark and Sweden must be dated. If the offerings from the Danish Bronze Age be examined it will be seen how a gradual change-over occurs from the Early to the Later Bronze Age from distinctly masculine to distinctly feminine objects 13). In the First Period of the Bronze Age masculine objects completely dominate, whereas in the Second Period they form only about 40 % and in the Third Period about 20 % of all offerings. In the Fourth Period they show a rise to about 40 %, while the percentage in the Fifth and Sixth Periods is respectively 25 and 10 %- These figures appear to agree with the fact that the first representations of the female divinity appear in the Fourth Period 14), while the earliest corresponding male figure appears as early as the Second Period 15). Even if undue weight should not he laid on the sparse surviving material from the Bronze Age of human figures in the round, there is still reason to underline the fact that female figures dominate in the Later Bronze Age; it should, however, be added that the torques, which are the objects which cause the high percentage of feminine objects in the Later Bronze Age, are also worn by male divinities, though singly, as can be seen in the case of the axe-bearing twin gods from Grevens Vænge in South Zealand 16). That the same female divinity lives on in the Early Iron Age is shown by discoveries of torques, and by the very stylized female figures which were worn as amulets in this period, and which still have the double torque represented around their necks (Fig. 11). It is possible that the noose still preserved around the necks of Tollund Man and Borremose Man should be seen as a token that they were both dedicated to the goddess with the torque. There is another feature of the peat bodies from the lron Age which could be interpreted as evidence that they were sacrifices to fertility divinities, in particular to gods of vegetation, but the material is unfortunately incapable of bearing any great weight, as it has only been possible to investigate so few specimens in sufficient detail. The last meal eaten by Tollund Man has been investigated in detail, and it appears that he had eaten only vegetable food 25), and the same seems to be the case with Grauballe Man 26), though his stomach contents are not yet fully investigated; this report will be published in a subsequent KUML. There is, it would seem, less reason to believe that the lron Age population were habitually vegetarians than to believe that the prospective sacrificial victims had eaten a special meal of vegetable food before being dedicated in death to a harvest goddess. P. V. Glob